1995
DOI: 10.1063/1.114484
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional exciton diffusion in GaAs quantum wires

Abstract: One-dimensional diffusion of excitons in GaAs quantum wires was observed by using microphotoluminescence measurements at low temperature. The observed diffusion length increased with decreasing wire width from 30 to 15 nm, and decreased from 15 to 7 nm, where maximum diffusion length was about 4 μm for the 15 nm quantum wire, which is the largest value so far reported. It is considered that the change of diffusion length versus wire width is caused by the competition between one-dimensional character and the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 0 publications
2
23
0
Order By: Relevance
“…[5], which is in agreement with the result presented here, there are, to the best of our knowledge, no ambipolar diffusion lengths reported for particle-seeded III-V NWs. However, we note that Nagamune et al [4] reported one of the longest exciton diffusion lengths, up to 2-4 mm, for GaAs wires. Their wires were quantum wires grown on V-grooves.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…[5], which is in agreement with the result presented here, there are, to the best of our knowledge, no ambipolar diffusion lengths reported for particle-seeded III-V NWs. However, we note that Nagamune et al [4] reported one of the longest exciton diffusion lengths, up to 2-4 mm, for GaAs wires. Their wires were quantum wires grown on V-grooves.…”
Section: Discussionmentioning
confidence: 95%
“…Using a Schottky contact and an electron beam, the diffusion of minority carriers in doped nanowires can be studied [3]. Local photo-excitation can also be used to study diffusion by photoluminescence imaging as long as the diffusion is longer than the excitation spot [4]. In this case, it is the combined diffusion of electrons and holes, the ambipolar diffusion, that is studied.…”
Section: Introductionmentioning
confidence: 99%
“…One-dimensional exciton diffusion in excess of several microns has been observed in GaAs quantum wires. 18 In our case, exciton diffusion is likely driven by the potential gradient due to the Al distribution seen in Figures 2 and 3. The full width at half maximum (FWHM) of the μPL spectra was 62 meV at 10 K, and 120 meV at 300 K, significantly greater compared to the expected thermal broadening.…”
mentioning
confidence: 99%
“…The excitation beam profile was shaped into a ring in real space with the use of two axicons and was projected to the microcavity through an objective lens (NA = 0.4) creating a polariton ring with a mean diameter of ∼ 20 µm on the sample (Supplementary Information, ?? ), which is of the order of the polariton mean free path in planar microcavities and much larger than the exciton diffusion length of the quantum wells of our sample [20,21]. The excitation beam intensity was modulated with an acousto-optic modulator at 1% duty cycle with a frequency of 10 kHz to reduce heating.…”
mentioning
confidence: 99%